Wall shear stress and oscillatory shear index measured using ultrasound vector flow imaging in the femoropopliteal artery of adults without peripheral artery disease - Gao, Meiying; Zheng, Haining; Zhao, Rui; Liu, Yan; Fang, Lizhu; Du, Yigang; Wen, Chaoyang; Tong, Yisha (Frontiers in Surgery, 2025)
ObjectiveTo measure wall shear stress (WSS), oscillatory shear index (OSI) and relative residence time (RRT) at multiple locations along the femoropopliteal artery in adults without peripheral artery disease (PAD), and to investigate whether low WSS, high OSI and/or high RRT are present in regions with a high prevalence of atherosclerotic lesions.Materials and methodsA total of 116 presumed healthy adult volunteers were recruited. Ankle-brachial index and lower-limb arterial duplex ultrasound assessments were performed to exclude participants with PAD. Maximum WSS, mean WSS, and OSI were measured at the near and far walls of ten arterial sites along the femoropopliteal artery using ultrasound vector flow imaging (VFI). RRT was calculated from OSI and mean WSS values obtained via VFI.ResultsA total of 113 participants (46 males and 67 females; 222 lower limbs), with a mean age of 37.6 years, were included in the analysis. Compared to the overall mean values across all 20 measurement sites, significantly higher OSI and higher RRT were recorded at the posterior wall of the common femoral artery (P < 0.01), while significantly lower WSS, higher OSI, and higher RRT were observed at the posterior wall of the femoral artery bifurcation (P < 0.01). The distal superficial femoral artery (SFA) at the adductor canal demonstrated significantly lower WSS and higher OSI at both near and far walls (P < 0.01). When comparing hemodynamic indices between sexes, males exhibited significantly lower WSS at several near-wall sites, significantly higher OSI at multiple near- and far-wall sites, and significantly higher RRT at the near wall of the proximal SFA and the far wall of the profunda femoris artery (P < 0.05).ConclusionsVariations in WSS, OSI, and RRT are evident along the femoropopliteal artery in adults without PAD. Notably, the distal SFA at the adductor canal demonstrated significantly lower and more oscillatory WSS, consistent with the region's reported high prevalence of atherosclerotic plaque and occlusion. Whether these hemodynamic patterns contribute to lesion development later in life remains uncertain and warrants further investigation.